Luttinger liquid and polaronic effects in electron transport through a molecular transistor: Carbon nanotubes, quantum wires and Luttinger liquid - Skorobagat’ko, G.A.; Krive, I.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Electron transport through a single-level quantum weakly dot coupled to Luttinger liquid leads is considered in the master equation approach. It is shown that for a weak or moderately strong interaction the differential conductance demonstrates resonant-like behavior as a function of bias and gate voltages. The inelastic channels associated with vibron-assisted electron tunnelling can even dominate electron transport for a certain region of interaction strength. In the limit of strong interaction resonant behavior disappears and the differential conductance scales as a power low on temperature (linear regime) or on bias voltage (nonlinear regime).